Analysis the Effect of Different Fluid Temperature and Pressure to The Flow and Pipe Structure Longevity for Plant Pipeline - Sahizan, Akif Akmal Hakimi (Progress in Engineering Application and Technology, 2022)
Pipes are widely used in many fields, such as construction sites, homes, and many fields including power plants. Under some conditions, stress generated by the inlet pressure of the desired fluid in the pipeline might cause stress distribution, which can lead to material crack and fracture failure. The piping system of a power plant can be classified as one of the key components of the power plant because it performs the task of transferring fluid from one process to another. The purpose of this study is to analyze the influence of different fluid temperatures (27℃ and 77℃) and three different pressures inlet (153kPa, 200kPa and 250kPa) to the pipe flow behavior and pipe structural performance. The layout 3D model for the pipeline is based on the pipeline used at the UTHM Biodiesel Plant starting from the esterification process until trans-esterification process. Result of the study is to identify the location in pipe that handle the highest stress distribution. ANSYS 19.2 software were used to conduct the simulation to determine the velocity, pressure and stress distribution. The result from the simulation shows that at pressure inlet 250kPa, the highest stress distribution located at fitting 10 with the value of stress is 3.045MPa.